Penanganan Stunting di Desa Candisari Dengan Peningkatan Produksi Telur Ayam Kampung Mendukung Program Dinas Kesehatan Kabupaten Magelang “Gaspoldulur” - Rasminati, Nur; Utomo, Setyo; Sudrajat, Ajat; Purwani, Tyastuti; Ismail, Fazhana (Unpad Press, 2024)
Stunting is a serious problem and needs to be solved properly, in order to improve the quality of health and good human resources. This service aims to help the government program of Candisari Village, Magelang in overcoming stunting. This service will be held in July-August 2023 in Candisari Village, Windusari, Magelang, Central Java and was attended by participants consisting of parents of toddlers affected by stunting. The method of implementing service is carried out by providing counseling on native chicken cultivation, distribution of hens and direct practice. The implementation stages start from coordinating activities, socialization and material presentation followed by a question and answer session. Then good native chicken maintenance management practices are carried out. The results of the service show that the knowledge of residents has increased as well as being more motivated in the production of family animal protein through the production of native chicken eggs, after this program runs residents who receive the help of the hen mother are now producing eggs every day and protein needs for toddlers independently can be met. It was concluded that the results of the service could increase knowledge and skills in residents and could help the Candisari Village government in handling stunting.